Answer:
-1/5
Step-by-step explanation:
We get this answer from substitution
Answer: it going to be 10.2% percent
Step-by-step explanation: that how you get your answer as your -
10.2 %
Answer:
r+p=-8
Step-by-step explanation:
5-p=r-3
5+3-p-r=0
8-p-r=0
r+p=-8
Answer:
5
Step-by-step explanation:
first multiply 3 by 7 as 3x7=21
again find the square of 4 as 4^2=16
finally, subtract 16 from 21 as 21-16= 5
Answer:
![k=1\text{ or } k=4](https://tex.z-dn.net/?f=k%3D1%5Ctext%7B%20or%20%7D%20k%3D4)
Step-by-step explanation:
We can use the Polynomial Remainder Theorem. It states that if we divide a polynomial P(x) by a <em>binomial</em> in the form (x - a), then our remainder will be P(a).
We are dividing:
![(x^2+5x+7)\div(x+k)](https://tex.z-dn.net/?f=%28x%5E2%2B5x%2B7%29%5Cdiv%28x%2Bk%29)
So, a polynomial by a binomial factor.
Our factor is (x + k) or (x - (-k)). Using the form (x - a), our a = -k.
We want our remainder to be 3. So, P(a)=P(-k)=3.
Therefore:
![(-k)^2+5(-k)+7=3](https://tex.z-dn.net/?f=%28-k%29%5E2%2B5%28-k%29%2B7%3D3)
Simplify:
![k^2-5k+7=3](https://tex.z-dn.net/?f=k%5E2-5k%2B7%3D3)
Solve for <em>k</em>. Subtract 3 from both sides:
![k^2-5k+4=0](https://tex.z-dn.net/?f=k%5E2-5k%2B4%3D0)
Factor:
![(k-1)(k-4)=0](https://tex.z-dn.net/?f=%28k-1%29%28k-4%29%3D0)
Zero Product Property:
![k-1=0\text{ or } k-4=0](https://tex.z-dn.net/?f=k-1%3D0%5Ctext%7B%20or%20%7D%20k-4%3D0)
Solve:
![k=1\text{ or } k=4](https://tex.z-dn.net/?f=k%3D1%5Ctext%7B%20or%20%7D%20k%3D4)
So, either of the two expressions:
![(x^2+5x+7)\div(x+1)\text{ or } (x^2+5x+7)\div(x+4)](https://tex.z-dn.net/?f=%28x%5E2%2B5x%2B7%29%5Cdiv%28x%2B1%29%5Ctext%7B%20or%20%7D%20%28x%5E2%2B5x%2B7%29%5Cdiv%28x%2B4%29)
Will yield 3 as the remainder.